Evaluation tool of land suitability for medicinal plants - Rahim, Supli Effendi; Supli, Ahmad Affandi; Damiri, Nurhayati; Zaman, Chairil; Husin, Husin (Graduate School, Sriwijaya University, Indonesia, 2019)
Planting medicinal crops must be carried out on a land that is suitable based on the results of a land suitability evaluation. A framework to evaluate the land suitability is initiated by FAO. Smart phone nowadays becomes ubiquitous technology to solve problems in most settings, such as agriculture, medicine, and many others. This paper is to capitalize such advantage by converting the framework into a mobile app. This solution is hoped to help land users to be more effective and efficient in evaluating their land. An algorithm is employed in the form the Rule Based System (RBS) in a way to construct the framework into bunch of rules that connect each other, resulting the conclusion of suitability. The rules itself are working on annual rainfall, altitude, drainage, soils’ type, pH, flood risk, fertility of the soils, soil solum depth, etc. This study focuses on three medicinal crops only, which are candlenut, cardamom and onion to be evaluated. Data of agro climatic that were determining the suitability of the crops were developed into general and specific criteria for the plants. A usability model was studied from 40 respondents using the app. The usability of the app was in “very good” classification.